Metode Kritis Al-Shawkani dalam Kitab Nayl Al-Awtar - Zainuddin Zainuddin MZ (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2009)
Of the many sources for the study of Had?th and the science of law and legal arrangements (al-ahkam wa al-mawaid), Kitab Muntaqa al-Akhb?r by Majd al-D?n Abd al-Sal?m bin Abdullah bin Qasim better known as Ibn Taymiyyah (d. 652 H) is one of the most important. This book has been commented by al-Shawkani in a book called Nayl al-Aw?r where he employs the following methods. First, elaborating and commenting not of all hadiths but some them in each chapter of the book. Second, describing the narrators of the hadiths, their quality and personality. Third, providing the literal meaning of the had?ths he commented. Fourth, explaining the grammatical position of the vocabularies of the had?th. Fifth, highlighting the use and benefit of the had?th. Sixth, explaining the views of various ulama on a hadith. Seventh, extrapolating the legal rules of the had?th using the dictums of the usul al-fiqh. This paper is designed to discuss this. It holds that in providing the commentary of the hadith, al-Shawkani begins with the issue of how it was narrated (takhr?j), and ends up with extrapolating rules that may be learnt from it. The paper also believes that al-Shawk?n? is an objective scholar, who worked in the elaboration and commentary of the had?ths just for the sake of knowledge. The fact that he often offers a commentary against the legal position of his own school of thought indicates that al-Shawk?n? a person of academic integrity. The methods that he employs and the spirit behind his determination to provide commentary, all point to one thing of particular importance, that al-Shawk?n? is immune of fanaticism and imitation.